Sustainable livelihood security through apiculture in the tribal tracts of West Godavari district of Andhra Pradesh - Prasad, J V; Karunasri, E; Raju, Shali; Meera, Shaik N (Indian Farming, 2024)
In the mono-cropped tribal dominant villages of West Godavari district in Andhra Pradesh, collection of honey from wild bee colonies has been a major source of income during the non-cropped rabi season. This skill of collecting honey has been on a decline among the tribal youth over years. In order to ensure sustained livelihood security to tribal farmers during the lean months of the year, an ICAR project under Tribal Sub Plan (TSP) was launched by the Krishi Vigyan Kendra (KVK), West Godavari (V R Gudem) covering 11 villages in 2 tribal mandals viz. Velerupadu and Buttaigudem in convergence with ITDA and an NGO Raithu Nestam. The villages were selected mainly based on the abundant forage availability. Three skill training programmes on all aspects of bee keeping were organized by the KVK and the trainees were provided with Italian bee (Apis mellifera) bee hive boxes (2 each), Indian bee (Apis cerana indica) bee hive box (1 each), comb foundation sheets and 4 honey extractors per cluster. Regular monitoring visits were made to handhold the tribal youth and to clear doubts if any on hive maintenance. In collaboration with ITDA, K R Puram, 9 cluster groups were formed and together these clusters were registered as Giridhara Honey Producers Society for production, marketing of honey and strengthening of bee keeping. This successful intervention in tribal areas ensured an average additional earning of `19,000 per year to each tribal family. This success has triggered enthusiasm among tribal youth who have been expanding the activity by the division of the bee colonies. Support in the form of regular training, handholding for maintenance of colonies, value addition and provision of market linkages in the future will strengthen this entrepreneurial activity and ensure sustained livelihood security to the resource poor tribal youth of West Godavari district.